2002
DOI: 10.1007/s004250100665
|View full text |Cite
|
Sign up to set email alerts
|

Aspartic proteinases are expressed in pitchers of the carnivorous plant Nepenthes alata Blanco

Abstract: Carnivorous plants acquire significant amounts of nitrogen from insects. The tropical carnivorous plant Nepenthes accumulates acidic fluid containing aspartic proteinase (AP) in its trapping organs (pitchers), suggesting that the plant utilizes insect protein as a nitrogen source. Aspartic proteinases have been purified and characterized from sterile pitcher fluid of several species of Nepenthes; however, there is, as of yet, no information about sequence and expression of Nepenthes AP genes. To identify the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
60
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(64 citation statements)
references
References 29 publications
1
60
1
Order By: Relevance
“…Cluster roots of H. undulata exude acid phosphatases (20), and evidence for root-secreted proteases has been recently reported in several crop and wild species (21). Digestive glands of carnivorous plant Nepenthes alata also are known to secrete aspartic proteinases into the liquid of the pitcher (22). Our results confirm the notion that cluster roots of Hakea are active in enzyme exudation (20,23) and show that exudation of enzymes is not restricted to cluster roots.…”
Section: Discussionsupporting
confidence: 79%
“…Cluster roots of H. undulata exude acid phosphatases (20), and evidence for root-secreted proteases has been recently reported in several crop and wild species (21). Digestive glands of carnivorous plant Nepenthes alata also are known to secrete aspartic proteinases into the liquid of the pitcher (22). Our results confirm the notion that cluster roots of Hakea are active in enzyme exudation (20,23) and show that exudation of enzymes is not restricted to cluster roots.…”
Section: Discussionsupporting
confidence: 79%
“…In this fragmentation, two peptide bonds (Tyr 16 -Leu 17 and Phe 24 -Phe 25 ) were specifically cleaved. These cleavage sites are similar to those of aspartic proteinases (APs) from N. distillatoria (Athauda et al 1998), cardoon (Verı´ssimo et al 1998), wheat (Bleukx et al 1998), and barley (Kervinen et al 1993), suggesting that the peptide bonds were cleaved by AP(s) in the pitcher fluid of N. alata (the presence of AP activity in the pitcher fluid of N. alata is described elsewhere: An et al 2002). Amino acid analysis of the degradation products revealed that alanine, leucine, and tyrosine were released after 1, 3, and 12 h of incubation, respectively (Fig.…”
Section: Discussionmentioning
confidence: 83%
“…The slippery walls also prevent the prey from escaping and it eventually drowns in the fluid in zone 3 ( Fig. 1) containing digestive solutions and absorptive glands (Schulze et al 1997;An et al 2002aAn et al , 2002b.…”
Section: Introductionmentioning
confidence: 98%